Regional Security Network in South Asia: A Prescriptive Approach to Addressing Diverse Security Threats - Hussain, Raziq; Khan, Aamir (Pakistan Journal of Humanities and Social Sciences, 2023)
The precarious nature of the evolving global security order and the emergence of associated new buzzwords both in academia and policy circles clearly suggest that the international security environment has changed substantially. Regional and global security hazards have further diluted security situation around the world. States have taken a number of measures to cope with security challenges and strategic uncertainties, with largely unsatisfactory outcomes. In our view, a better alternative to traditional way of ensuring security is to develop regional security networks (RSN) among nations of a specific geographic region. RSN is based on the idea that there are various security challenges that cannot effectively be met without regional collaboration and coordination. The idea of RSN calls for, among other things, creating a collaborative platform for information sharing, joint training, and coordinated response mechanisms to address security threats in South Asia. Prescriptive in character, this article provides a strategic roadmap for policymakers to strengthen regional security cooperation and foster stability and peace in South Asia by establishing a robust RSN.